The becoming of English teacher educators in Australia: a cross-generational reflexive inquiry. (3rd March 2020) - Parr, Graham; Bulfin, Scott; Diamond, Fleur; Wood, Narelle; Owen, Ceridwen
ABSTRACT: As concerns spread about the capacity of teacher education programmes to prepare preservice teachers for entry into the teaching profession, literature and policy have begun to scrutinise the knowledge and skills of teacher educators. Some publications have focused on the professional development needed by teacher educators to align their teaching with standards-based reform policies. Little attention has been paid, though, to the complex ways teacher educators, individually and in communities, negotiate these policies in the course of their day-to-day practices. This qualitative study examines how standards-based reforms have come to dominate teacher education policy in the English speaking world, and how they have influenced the practices and identities of teacher educators over the past three decades. It employs reflexive autobiographical narratives written by five English teacher educators from different generations in one Australian university to investigate how their practices and identities are shaped by, or resistant to, the de-professionalising potential of standards-based reforms. The authors advocate for the concept of ideological becoming to better understand the formation and development of English teacher educators, and they identify a number of 'enablers' which can activate and sustain teacher educators' becoming throughout their careers.